Metode Simple Additive Weighting Untuk Pemilihan Sosial Media Pada Pemasaran Digital UMKM Kuliner Kota Banjarmasin - Rusidah, Rusidah; Nurhaeni, Nurhaeni; Hidayat, Ahmad; Mambang, Mambang (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
Digital marketing has become very important because the world of marketing has changed through advances in information technology. Interactive and integrated marketing that allows market intermediaries, potential consumers and producers to interact with each other. Instagram, WhatsApp, Twitter, Facebook, Telegram, TikTok, YouTube, and Shopee are social media that are often used in digital marketing. In this research, the data used is Banjarmasin City Culinary UMKM data obtained through a questionnaire totaling 174 respondent data which was distributed to the Banjarmasin City Culinary UMKM group. Data obtained from decision support system calculations using the Simple Additive Weighting method shows that many social media that are popular in society may not be suitable for use as digital media for culinary marketing. The results of the Simple Additive Weighting research show that it can be used to help culinary MSMEs in Banjarmasin City in making decisions about the use of social media through social media ranking results. This decision is reviewed based on several criteria such as length of business, length of use of social media, income and age. The length of business is because the longer the business lasts, the more people will know it. The length of use of social media is because the longer people use social media, the more they understand how to use the features and benefits of the features on social media. The greater the income in the business, the faster the business will develop. If you are at a more ideal age for running a business, your business will develop quickly because you have creative ideas and broad insight into business. The results of the Simple Additive Weighting method research show that WhatsApp has an accuracy value of 0.92, while Telegram has an accuracy value of 0.715. The concrete impact of the results of this research is that social media can help increase sales and the Simple Additive Weighting method can be used as a decision maker in selecting social media as a marketing medium so that Culinary MSMEs do not make the wrong choice in using social media.